A Compact Triple-Band Negative Permittivity Metamaterial for C, X-Band Applications - Dushyant Marathe; Kishore Kulat (International Journal of Antennas and Propagation)
We report a new design of triple-band electric metamaterial resonator (TBEMR) based on integration of open delta loops within square ring resonator. This metamaterial resonator has three distinct ε-negative regions (ENG) over C, X frequency bands. The transmission and reflection response of the proposed subwavelength resonator is analyzed using full-wave electromagnetic solver Ansys HFSS to demonstrate the presence of electrical resonances within frequencies 4–12 GHz. Effective medium parameters permittivity and permeability are extracted from simulated complex scattering parameters to verify existence of ENG regions. The investigations are also carried out regarding dependence of resonant frequencies on design parameters of the TBEMR unit cell. The effective medium ratio (λ0/a) for proposed subwavelength resonator is compared with various other metamaterial resonators to indicate its compact nature.